2010
DOI: 10.1016/j.jcrs.2010.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toric intraocular lenses and peripheral corneal relaxing incisions to treat astigmatism during cataract surgery

Abstract: Although refractive astigmatism decreased in both groups, toric IOL implantation was more effective and predictable, resulting in greater spectacle independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
90
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 25 publications
8
90
1
3
Order By: Relevance
“…(Mean reduction in our cases 39%) . Also Mingo had similar results with a mean reduction of 29% 20 . Higher reduction was shown by Fouda in 2010 21 .…”
Section: Misalignments and Rotationsupporting
confidence: 56%
See 1 more Smart Citation
“…(Mean reduction in our cases 39%) . Also Mingo had similar results with a mean reduction of 29% 20 . Higher reduction was shown by Fouda in 2010 21 .…”
Section: Misalignments and Rotationsupporting
confidence: 56%
“…The results indicated some regression of refractive astigmatism within the first 3 months of about 30 % of astigmatic correction. Regression was also noted by different surgeons .Mingo showed that preoperative refraction was reduced from -2.17±1.03D to postoperative refraction of -1.3±0.60D 20 . We thought this regression might be due to the healing process of the wound.…”
Section: Misalignments and Rotationmentioning
confidence: 86%
“…Each degree of rotation causes an average loss of cylinder power of approximately 3%; thus, when an IOL rotates 30 degrees there is no astigmatic correction, although there is a change of axis (44,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) . Articles comparing the use of toric IOL to other astigmatism reducing techniques, such as opposed clear corneal incisions (56) or LRI (57) , are still scanty in number on literature. Slightly advantageous outcomes, favoring toric IOL have been reported (56,57) , but debate on which technique unequivocally offers better results is just at the beginning.…”
Section: B) Non-incisional Approachmentioning
confidence: 99%
“…Articles comparing the use of toric IOL to other astigmatism reducing techniques, such as opposed clear corneal incisions (56) or LRI (57) , are still scanty in number on literature. Slightly advantageous outcomes, favoring toric IOL have been reported (56,57) , but debate on which technique unequivocally offers better results is just at the beginning. Toric IOL may also be employed in conjunction to such techniques aiming further refractive improvements (38) .…”
Section: B) Non-incisional Approachmentioning
confidence: 99%
“…[2][3][4] Tam bu noktada torik göz içi lensler (GİL) katarakt cerrahisi sonrası gözlük kullanmak istemeyen ya da camlarının kalınlığından şikayetçi olan hastalarda astigmatik kırma kusurunun düzel-tilmesinde sonuçları önceden tahmin edilebilir ve kolay uygulanabilir bir seçenek olarak karşımıza çıkmaktadır. 5,6 Torik GİL'ler katarakt cerrahisi dı-şında herhangi bir müdahaleye gerek kalmadan tek bir işlemle kataraktı ve astigmatizmayı tedavi etmeye olanak sağlar. Torik GİL'lerin düzeltilmesi hedeflenen keratometrik astigmatizma değerine göre değişen farklı alt tipleri mevcuttur.…”
unclassified